Análise da exposição pessoal ao material particulado atmosférico no sistema de transporte público urbano de Curitiba - Curti, Suzana Moreira Muniz (2018)
The present study aims to evaluate short-time personal-exposures to particles characterized by concentration [in number and mass] and by particles chemical elementary composition, existing at Curitiba’s public transportation routes. Five different bus-routes belonging to public transportation-system of Curitiba city (Brazil) were selected through data survey (URBS - Urbanização de Curitiba). Such routes presented the largest flow of people as compared to other routes in that city. Thin particular matter (PM) were collected on these main routes. Concentration in number of the particles with diameter cut off at 0.3, 0.5, 1.0 and 2.5 μm was determined. The particulate material was sampled by the personal equipment DataRAM pDR-1500 in a PTFE filter with 37 mm and PORO diameter of 2 μm, in similar conditions as the flow of the human respiratory system (3 L min-1), beyond a particles counter MetOne with the help of a GPS. Such apparatus were used in whole routs, during the sampling. Three runs were made for each selected route. For each run, the as-collected filter was further examined and quantified [through Energy Dispersive X-ray Fluorescence spectroscopy (EDX-RX)] to determine the elemental chemical composition from the sampled material; the Black Carbon elemental (BCe) was quantified by Reflectance. Most of the peak time MP2.5 concentrations were 18.4 to 23.7 μg m-3 and on off peak time were 9.9 to 14.2 μg m-3. The number particles with size below 0.3 μm (PN0.3) ranged from 240 to 330 particles cm-3 on the off peak time; and from 200 to 300 particles cm-3 on the peak time for each route. From the chemical elements in the sampled environment, three of them can be noticed according to the detected amount: i) Sulfur (S), concentrations: 1547.6 ng m-3on the peak time and 1710.3 ng m-3 on the off peak time; ii) Sodium (Na) concentrations: 2203.8 ng m-3 on the peak time and 1476.3 on the off peak time; and Iron (Fe) concentrations: 357.0 ng m-3 on the peak time and 497.8 ng m-3 on the off peak time. The concentration of Black Carbon elemental (BCe) changed from 7.43 to 16.19 μg m-3 on the off peak time; on the peak time it changed from 11.05 to 20 μg m-3.